Robotics in Healthcare: A Systematic Review of Robotic-Assisted Surgery and Rehabilitation (International Journal of Scientific Research in Science and Technology, 2024)
This paper comprehensively reviews robotic-assisted surgery and rehabilitation, highlighting the technological advancements, applications, and impacts on healthcare outcomes. Robotic systems offer unprecedented precision and efficiency in surgical procedures and rehabilitation therapies, improving patient outcomes and operational efficiency. The integration of artificial intelligence and machine learning further enhances the capabilities of these technologies, offering personalized treatment options and predictive insights. However, adopting robotic-assisted interventions presents challenges, including high costs, regulatory hurdles, and ethical considerations. Future directions emphasize the need for interdisciplinary research, innovation, and policy-making to address these challenges and expand the potential of robotics in healthcare. This review underscores the transformative impact of robotic technologies on medical practices and the imperative for ongoing education, regulation, and research to fully realize their benefits in enhancing patient care.
Keywords: Robotic-Assisted Surgery; Rehabilitation Robotics; Healthcare Technology; Artificial Intelligence